A descriptive analysis of emergency care provided in Northern Somalia - Muange, Dennis (Division of Emergency Medicine, 2020)
Emergency care is an integral part of an effective healthcare system. However, emergency care systems remain largely underdeveloped in low- and middle-income countries, particularly in Sub-Saharan Africa. Somalia is in the horn of Africa. Decades of civil war, political instability, and terrorism insurgency have greatly hampered healthcare in the country, and the country does not have a formal emergency care system. The aim of the study was to assess the current provision of emergency care in healthcare facilities in northern Somalia, namely Somaliland and Puntland. This was a cross-sectional descriptive study carried out in all emergency units in Hargeisa and Garowe, the capital cities of Somaliland and Puntland respectively. A standardised WHO emergency care assessment tool was used to assess the performance of emergency care procedures in the emergency units. Simple descriptive statistics were used to analyse the data. Six facilities - two in Puntland, and four in Somaliland - participated in the study. Two of these were regional referral public facilities, while the rest were private. The performance of sixty emergency care procedures was assessed. Absent equipment was the main reason (47%, n=60 for the non-performance of these emergency care procedures. Lack of training (29%), stock out of supplies (13%), and lack of skilled personnel (10%) were the other reasons for the non-performance of these emergency care procedures. The findings of this study underscore the need for more resource allocation with a focus on equipping emergency units and having adequate supplies. The study also highlights the need for training of healthcare providers who routinely provide care in emergency units.